P265 The effect of high frequency airway oscillations on the lung clearance index when compared to a placebo device. (12th November 2019) - Daynes, E; Greening, NJ; Owers-Bradley, J; Sidiqqui, S; Singh, SJ
Abstract : Introduction: It is reported that 2.7–33% of patients with COPD report sputum retention. This disparity is due to variability in outcomes. Current measures of sputum retention are labour intensive and with large variance, therefore there is a need for an objective measure. This study aims to explore the use of the Lung Clearance Index (LCI) as a surrogate measure of sputum clearance. Methods: Participants were recruited to complete the LCI as part of a randomised controlled trial. Participants used an oscillating device or a placebo for eight weeks. The LCI was derived from a multiple breath washout using an open circuit Innocor system using 0.2% sulphur hexafluoride (SF6). Participants breathed at tidal volumes and the washout was performed on room air. The test was terminated with participants reached 1/40th of the starting concentration. From the multiple breath washout the LCI and conducting and acinar slopes were analysed (Scond /Sacin ) Results: 104 participants were recruited to this study. 53% of participants reported ≥3 on the COPD assessment test (CAT) sputum scale. Patients with ≥3 or <3 on the CAT sputum scale had a similar LCI (10.0905, 10.4851 respectively) however demonstrated higher (worse) Sacin (0.693, 0.504) suggesting an alteration in peripheral airways. Those receiving the placebo had a greater deterioration of the LCI comparatively to the active group (+0.6059 placebo, +0.3693 active). The Sacin improved greater in the intervention group (-0.178 active, -0.0476 placebo). These results were amplified when analysed according to the CAT sputum score (LCI CAT ≥3 0.3423, CAT <3 0.4164, Sacin 0.2603, 0.0911). Conclusion: During the study phase, both groups saw a worsening of their LCI however those receiving the active treatment had a better preservation of this. The Sacin improved greater in those using the active treatment and this was amplified when analysed in those with higher self-reported sputum.